Two steps forward : a story of persevering in hope - Brown, Sharon Garlough (IVP Books, An Imprint of InterVarsity Press, 2015)
Meg, Charissa, Hannah, and Mara are taking their next steps in the spiritual formation journey. But each is finding a roadblock-- and sometimes life feels like two steps forward and one step back. Can they help each other overcome the griefs and tensions that keep resurfacing?